Cultural Diversity of Local Communities to Create Galunggung Geopark in Tasikmalaya Regency - Cahya Darmawan; Siti Fadjarajani; Iman Hilman (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2021)
Geopark Galunggung is a platform that accommodates the various potentials of the Kabuapaten Tasikmalaya, in the aspects of geodiversity, biodiversity and cultural diversity. To be able to realize the Galunggung Geopark, active interaction of the local community is required to maintain and preserve the cultural diversity of the geopark area. This study includes four sub-districts namely Leuwisari, Sariwangi, Sukaratu and Padakembang Districts. These four sub-districts are areas that have a lot of diversity in potential compared to other regions. The method used in this research is descriptive method with a qualitative approach and phenomenological studies. Observation data techniques, interviews, documentation study and literature study. The results of this study, the cultural diversity that exists in society is tangible (tangbile) and intangible (intangible), but conditions in the field have a lot of cultural diversity that has almost disappeared due to the times.